Crash reduction factors for traffic engineering and intelligent transportation system (ITS improvements) state-of knowledge report. - Harkey, David L. (Research results digest (National Cooperative Highway Research Program ), 2005)
"This digest is an interim deliverable from NCHRP Project 17-25, 'Crash reduction factors for traffic engineering and ITS improvements,' which is being carried out under a contract with The University of North Carolina Highway Safety Research Center (HSRC) under the direction of David L. Harkey (Principal Investigator)."--P. [1].